Bone Mineral Density, Balance Performance, Balance Self-Efficacy, and Falls in Breast Cancer Survivors With and Without Qigong Training: An Observational Study - Shirley S. M. Fong PhD, PT; Anna W. M. Choi PhD, RSW; W. S. Luk MD; Timothy T. T. Yam MPT, PT; Joyce C. Y. Leung MN, RN; Joanne W. Y. Chung PhD, RN (Integrative Cancer Therapies, 2018)
Purpose: A deterioration in bone strength and balance performance after breast cancer treatment can result in injurious falls. Therefore, interventions need to be developed to improve the bone strength and balance ability of breast cancer survivors. This cross-sectional exploratory study aimed to compare the bone mineral density (BMD), balance performance, balance self-efficacy, and number of falls between breast cancer survivors who practiced qigong, breast cancer survivors who did not practice qigong, and healthy individuals. Methods: The study included 40 breast cancer survivors with more than 3 months of qigong experience, 17 breast cancer survivors with no qigong experience, and 36 healthy controls. All the participants underwent dual-energy X-ray absorptiometry scans to measure their lumbar spine, total hip, femoral neck, and total radius BMDs. The participants also underwent a timed one-leg stand test to measure their single-leg standing balance. The participants’ balance self-efficacy was assessed using the activities-specific balance confidence scale, and the number of falls experienced by each participant was assessed in a face-to-face interview. Results: The lumbar spine, total hip, femoral neck, and total radius BMDs were similar between the 3 groups ( P > .05). The breast cancer-qigong group outperformed the breast cancer-control group by 27.3% when they performed the one-leg stand test on a foam surface ( P = .025), and they also had a higher balance self-efficacy score ( P = .006). Nevertheless, the numbers of falls were comparable between the 3 groups ( P > .05). Conclusion: Qigong may be a suitable exercise for improving the balance performance and balance self-efficacy of breast cancer survivors.